EFEKTIVITAS KONSELING KELOMPOK TERHADAP KEJENUHAN BELAJAR MAHASISWA BIMBINGAN PENYULUHAN ISLAM UIN SUMATERA UTARA - muhammad fadhil; Muhammad Putra Dinata Saragi; Nurul Hidayah; Suwan Pradona (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Saturation of learning is something that must be felt by students. Students often experience the name saturation in learning. This problem needs to be overcome so that students are not lazy in achieving what they have aspired to. This type of research uses a type of qualitative research which This study aims: (1) To find out whether by conducting group counseling can overcome student problems in dealing with learning boredom. (2) To find out how effective the results are after students conduct group counseling. The subjects of this study were students where the researcher collected eight students as samples to carry out the group counseling process about boredom in learning. This research method uses qualitative methods. Data collection techniques used are observation and interviews. The results and discussion are how to prevent students from getting bored in doing learning by using group counseling services as a solution. Group counseling activities are able to provide the right choices and results to anticipate and prevent learning saturation for these students.